The non-native English speaker teachers in TESOL movement. (30th March 2016) - Kamhi-Stein, Lía D.
Abstract: It has been almost 20 years since what is known as the non-native English-speaking (NNES) professionals' movement—designed to increase the status of NNES professionals—started within the US-based TESOL International Association. However, still missing from the literature is an understanding of what a movement is, and why non-native English speaker teachers (NNESTs) in TESOL constitute a movement. This article draws on the field of sociology to explain the notion of a 'movement' and explains the emergence of the NNEST movement as a sociological phenomenon. The article further discusses the NNEST movement's achievements in creating opportunities for leadership development, and research and publications; its partial achievements in providing NNES professionals networking opportunities; and its failure in promoting a more inclusive environment for NNES professionals. The article ends with a call for action.